EFEKTIVITAS PEMANFAATAN ALOKASI DANA DESA BAGI PEMBERDAYAAN MASYARAKAT DAN INFRASTRUKTUR PEDESAAN DI DESA WAYAME KECAMATAN TELUK AMBON - Ferdinandus, Sherly (Equilibrium: Journal of Economics and Development Studies, 2024)
Effectiveness of Utilizing Village Fund Allocations for community Empowerment and Rural Infrastructure in Wayame Village, Teluk Ambon District". This research aims to determine the benefits of village fund allocation for economic development and rural infrastructure in Wayame Village, Teluk Ambon District. Qualitative descriptive research with data collection techniques through observation, interviews and documentation. Analysis of the data obtained is in the form of quantitative and qualitative analysis. The results of this research are that the economic and infrastructure development program that was realized in Wayame village, Teluk Ambon subdistrict can be seen from several stages, namely the stages of achieving goals, adaptation and implementation, everything runs on time and is also implemented well so that the benefits of Village Fund Allocation for economic and infrastructure development in Wayame village, Teluk Ambon sub-district, namely the community becomes prosperous, the village also becomes advanced, and development in Wayame village, Teluk Ambon sub-district, becomes better.